(untitled) (New York, 1998)
Provides readers with a solid background in the theories of economic geography, while examining contemporary issues. Updated edition integrates new recent research on industrial geography using information published within the last ten years with an added global emphasis. Features a new chapter on interdependent global economies and improved figures and graphics, including updated tables throughout the text.
Keywords: Địa lý kinh tế,Economic geography